Sabar Dan Syukur Menurut Ulya Ali Ubaid Dalam Perspektif Pendidikan Islam - Siti Maesaroh; Imam Muslih (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2023)
This study aims to describe Patience and Gratitude According to Ulya Ali Ubaid the Perspective of Islamic Education. The approach used in this study is an analytic descriptive approach where after the data is collected, the data is sorted and classified and then categorized according to the theme raised. The reason for using this approach is to get a comprehensive picture of the object under study and to know Patience and Gratitude According to Ulya ali Ubaid the Perspective of Islamic Education contained in the book Patience and Gratitude The Gate of Happiness in the World and the Hereafter. data collection, researchers examine various kinds of books (Primary and Secondary), or other written data, which are relevant to the title. The method used in analyzing the data in this study is to use a descriptive method that describes Patience and Gratitude According to Ulya Ali Ubaid Perspective of Islamic Education. The results of his research are Patience and Gratitude According to Ulya Ali Ubaid Perspective of Islamic Education.Patience is pushing the soul and moving the body to achieve the desired goals to reach the gates of happiness for a servant. Patience is not giving up on circumstances without any effort to get up, and without knowing that we are indeed given the opportunity to do good deeds and work better than the previous days. while gratitude is showing or describing a favor and showing it. The way to be grateful for the blessings of faith and Islam is by: being grateful with the heart, being grateful with speech, being grateful with deeds, being grateful with wealth, the foundation of good deeds, namely: sincere, bala' or the test of Allah, Keeping Oral, Honest, Piety and Trust